2005
DOI: 10.1097/01.jcp.0000155816.21467.25
|View full text |Cite
|
Sign up to set email alerts
|

Does Modafinil Enhance Cognitive Performance in Young Volunteers Who Are Not Sleep-Deprived?

Abstract: In a double-blind, parallel groups study, 60 healthy student volunteers (29 men and 31 women, aged 19-22 years) were randomly allocated to receive placebo, 100 or 200 mg modafinil. Two hours later, in the early evening, they completed an extensive cognitive battery. The 3 groups did not differ in self-ratings of sleepiness or tiredness before the testing session, and there were no treatment-associated changes in these or in mood ratings during the tests. Modafinil was without effect in several tests of reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 8 publications
4
85
2
1
Order By: Relevance
“…Modafinil also improved performance during day-shift work but to a lesser degree. This observation is in line with other researchers who found that the drug produced limited effects on cognitive performance in healthy, well-rested individuals (eg, Muller et al, 2004;Randall et al, 2004Randall et al, , 2005. By contrast, modafinil produced greater sleep disruptions when participants worked on the day shift than when they worked on the night shift.…”
Section: Discussionsupporting
confidence: 79%
“…Modafinil also improved performance during day-shift work but to a lesser degree. This observation is in line with other researchers who found that the drug produced limited effects on cognitive performance in healthy, well-rested individuals (eg, Muller et al, 2004;Randall et al, 2004Randall et al, , 2005. By contrast, modafinil produced greater sleep disruptions when participants worked on the day shift than when they worked on the night shift.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, modafinil could not be considered as a cognitive enhancer in non sleep-deprived healthy subjects (Randall et al, 2005). On the opposite, previous results of our laboratory obtained on healthy sleepdeprived adults (after a 60-hr sleep deprivation period) showed that modafinil is able to restore the overall psychomotor performance to the non sleep-deprived levels (Lagarde and…”
Section: Discussionmentioning
confidence: 59%
“…Low-dose modafinil does not reliably enhance cognitive task performance in non-sleepdeprived subjects (32,33). Similarly, the drug's efficacy to reduce subjective and objective measures of sleepiness after sleep deprivation differs widely among individuals (22).…”
Section: Discussionmentioning
confidence: 99%